The Beneficial Effects of Bisphosphonate-enoxacin on Cortical Bone Mass and Strength in Ovariectomized Rats - Liu, Xuqiang; Qu, Xinhua; Nie, Tao; Zhai, Zanjing; Li, Haowei; Ouyang, Zhengxiao; Qin, An; Zhang, Shuhong; Zhang, Shuangyan; Fan, Qiming; Tang, Tingting; Yu, Zhifeng; et al. (Frontiers in Pharmacology, 2017)
Osteoporosis is a major age-related bone disease characterized by low bone mineral density and a high risk of fractures. Bisphosphonates are considered as effective agents treating osteoporosis. However, long-term use of bisphosphonates is associated with some serious side effects, which limits the widespread clinical use of bisphosphonates. Here, we demonstrate a novel type of bone-targeting anti-resorptive agent, bisphosphonate-enoxacin (BE). In this study, ovariectomized rat model was established and treated with PBS, zoledronate (50 μg/kg) and different dose of BE (5 mg/kg and 10 mg/kg), respectively. The rats subjected to sham-operation and PBS treatment were considered as control group. Then, micro-computed tomography scanning, biomechanical tests, nano-indentation test and Raman analysis were used to compare the effects of zoledronate and BE on cortical bone mass, strength, and composition in ovariectomized rats. We found that both zoledronate and BE were beneficial to cortical bone strength. Three-point bending and nano-indentation tests showed that zoledronate- and BE-treated groups had superior general and local biomechanical properties compared to the ovariectomized groups. Interestingly, it seemed that BE-treated group got a better biomechanical property than the zoledronate-treated group. Also, BE-treated group showed significantly increased proteoglycan content compared with the zoledronate-treated group. We hypothesized that the increased bone strength and biomechanical properties was due to altered bone composition after treatment with BE. BE, a new bone-targeting agent, may be considered a more suitable anti-resorptive agent to treat osteoporosis and other bone diseases associated with decreased bone mass.